Poly-ε-caprolactone electrospun nanofiber mesh as a gene delivery tool - Jianhao Jiang; Muhammet Ceylan; Yi Zheng; Li Yao; Ramazan Asmatulu; Shang-You Yang (AIMS Bioengineering, 2016)
Poly-ε-caprolactone (PCL) is a biodegradable aliphatic polyester which plays critical roles in tissue engineering, such as scaffolds, drug and protein delivery vehicles. PCL nanofiber meshes fabricated by electrospinning technology have been widely used in recent decade. The objective of this study intends to develop a gene-tethering PCL-nanofiber mesh that can be used as a wrapping material during surgical removal of primary bone tumors, and as a gene delivery tool to provide therapeutic means for tumor recurrence. Non-viral plasmid vector encoding green fluorescent protein (eGFP) was incorporated into PCL nanofibers by electron-spinning technique to form multilayer nano-meshes. Our data demonstrated that PCL nanofiber mesh possessed benign biocompatibility in vitro. More importantly, pCMVb-GFP plasmid-linked electrospun nanofiber mesh successfully released the GFP marker gene and incorporated into the co-cultured fibroblast cells, and consequently expressed the transgene product at transcriptional and translational levels. Further investigation is warranted to characterize the therapeutic influence and long-term safety issue of the PCL nanofiber mesh as a gene delivery tool and therapeutic device in orthopedic oncology.